FACTORS INFLUENCING THE SPORTS INVOLVEMENT OF SEPAK TAKRAW ATHLETES IN A STATE UNIVERSITY - Panganiban, Teejay D; Manalo, Rommel P; Polgado, April Kisses S; Sarmiento, Marc John H (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This research study focused on the factors influencing the sports involvement of Sepak Takraw athletes of Batangas State University- JPLPC Campus. It made use of the descriptive method of research. The respondents were 35 varsity players of Batangas State University- JPLPC Campus for the Academic Year 2014-2015. Percentage, weighted mean and chi-square test were utilized in the study. After careful analysis and interpretation of data, it was found out that majority of the factors are involved in playing Sepak Takraw. The respondents performed moderately high in their chosen sports. Likewise, there is a significant difference between the factors influencing the sports involvement of the respondents and their profile. The findings of the study helped the respondents to do their passion and gained the enjoyment in playing the Sepak Takraw. They were also given a chance to pursue their dreams and studies by the scholarship and incentives from the program of the school. With this study, the coaches were able to identify the weaknesses and strength of the players and their needs. In view of the problem in this endeavor, the following actions were proposed by the researchers. The school personnel may consider these factors and assess the capability of each player:, the school may initiate seminars and trainings such as Sepak Takraw Sports Clinic for teachers as well as for students: It may conduct and supervise the training of athletes and organize leadership trainings and/or team building activities for moral and spiritual development of the players: In addition, they may create activities that would enhance the students’ skills to facilitate difficulties they encounter regarding this sports: Lastly, they may allocate enough budgets to help realize and actualize the goals of the program. This may be done through the approval of the administration to procure the needed resources through the Annual Procurement Plan prepared by the Sports Director/ Heads: The Sports Coordinator may enhance the scholarship program to encourage more players to join this sport, enhance training programs and promote the organization that administers this sport.